Hormonal regulation of the transformation phenotype in simian virus 40-transformed rat embryonic preadipose cell lines. - Yasumoto, S (1984)
The regulation of transformed phenotypes was studied in newly isolated preadipose cell lines which were established after infection with simian virus 40 tsA58 dl2009. The clonal cell lines isolated exhibited most of the characteristics typical of transformed cells. The transformants, however, were able to differentiate into adipocytes in the presence of low calf serum (0.5%) and a combination of several hormones, including hydrocortisone and insulin. Treatment with insulin alone stimulated the growth of these cells but did not induce lipid accumulation without added hydrocortisone. The effect of hydrocortisone was accompanied by a restoration of growth control in the transformants after they reached high cell density. The blot hybridization analysis of cellular DNAs digested by restriction enzymes revealed that simian virus 40 genomes were integrated at multiple separate sites at which a head-to-tail oligomeric insertion took place. Large T antigen was synthesized in growing cells but was regulated at high cell density when cells were committed to differentiate by glucocorticoids. These results suggest that the glucocorticoid hydrocortisone is capable of restoring growth regulation at high cell densities to simian virus 40-transformed preadipose cell lines.